2014
DOI: 10.1016/j.stemcr.2014.10.002
|View full text |Cite
|
Sign up to set email alerts
|

RB Maintains Quiescence and Prevents Premature Senescence through Upregulation of DNMT1 in Mesenchymal Stromal Cells

Abstract: SummaryMany cell therapies currently being tested are based on mesenchymal stromal cells (MSCs). However, MSCs start to enter the senescent state upon long-term expansion. The role of retinoblastoma (RB) protein in regulating MSC properties is not well studied. Here, we show that RB levels are higher in early-passage MSCs compared with late-passage MSCs. RB knockdown induces premature senescence and reduced differentiation potentials in early-passage MSCs. RB overexpression inhibits senescence and increases di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 24 publications
2
32
0
Order By: Relevance
“…Quiescence serves an essential role in preserving stem cell function until the stem cell is needed in tissue homeostasis or repair. Cell quiescence and proliferation are tightly regulated to maintain tissue homeostasis (Coller, 2011; Hilpert et al, 2014; Lin et al, 2014; Rodgers et al, 2014). The reactivation of qNSCs into proliferation is crucial for tissue repair and regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Quiescence serves an essential role in preserving stem cell function until the stem cell is needed in tissue homeostasis or repair. Cell quiescence and proliferation are tightly regulated to maintain tissue homeostasis (Coller, 2011; Hilpert et al, 2014; Lin et al, 2014; Rodgers et al, 2014). The reactivation of qNSCs into proliferation is crucial for tissue repair and regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…DNMT1 knockdown in early-passage MSCs induces senescence and reduces differentiation potential through a pRB-mediated pathway, whereas DNMT1 overexpression in late-passage MSCs prevents senescence [25]. Other studies demonstrated that the inhibition of DNMT1 in MSCs prevents differentiation to osteoblasts, adipocytes or chondrocytes by inducing replicative senescence mediated by p16 and p21 expression [26].…”
Section: Introductionmentioning
confidence: 99%
“…The written informed consent was obtained from donors to participate in this study before clinical procedure. Primary hBMSCs were collected from patients who received an orthopedic surgery as described previously . For rapid expansion in low‐density culture, hBMSCs were grown in complete culture medium (CCM; α‐minimal essential medium supplemented with 16.6% fetal bovine serum [FBS], 100 units/mL penicillin, 100 µg/mL streptomycin, and 2 mM l ‐glutamine).…”
Section: Methodsmentioning
confidence: 99%